Sistem Informasi Geografis Pemetaan Menara Telekomunikasi dengan Pengecekan Jarak Menggunakan Metode Haversine - Arba'i, Sultan; Wedhasmara, Ari; Fathoni, Fathoni; Putra, Apriansyah; Kurniawan, Dedy (Maranatha University Press, 2023)
DISKOMINFO OKU Regency provides recommendations for the establishment of telecommunication towers. Then do the planning and arrangement of telecommunication towers. However, this is still done manually based on map visualization in printed books, so when changes occur, you have to reprint the book, and you have to re-plan with Microsoft Excel, which makes the process more difficult and time consuming. In addition, there is no digital tower information service causing a lack of information for tower providers, so that the construction of towers has not been properly organized. So the solution to this problem is to build a system that can manage data, can map telecommunication towers and can plan the need for shared towers for the next 5 years by taking into account population, cellular service users, traffic requirements, number of BTS and tower coverage radius, and can provides information on checking coordinates by applying the haversine method which is useful so that the construction of new towers can be properly arranged in the system, where the system is made based on a website with a design using the waterfall method. The results of this study are an application that can assist the process of planning and arrangement of towers, both visual maps, tower requirements, checking coordinates and so on, which is done computerized.